A PORTRAIT OF A PRINCESS IN SOCIETY IN MORTON’S DIANA: HER TRUE STORY – IN HER OWN WORDS (A BIOGRAPHICAL ANALYSIS) - Sagita K. Mangolo (JELLT (Journal of English Language and Literature Teaching), 2020)
The purpose of this research is to reveal about Princess Diana’s role in society in Andrew Morton Diana: Her True Story – In Her Own Words. This research is classified as a qualitative research. The data gathered are in the form of words as well as quotation. The writer collects the data from two kinds of sources namely primary source and secondary. The primary data source was taken from the Biography book Diana: Her True Story – In Her Own Words by Andrew Morton. And the secondary source is other material that supports the analysis, such as website. The result of this study shows the role of Princess Diana in society. Diana as a Princess actives in humanitarian activities, she was always seen visit and entertain AIDS sufferers, leprosy and other diseases, she also actively visited homeless people in shelters, she was active in supporting human welfare, and actively raised funds and formed charities to help people who need help. The one thing that Diana had done that shocked the world at the time was when she broke the stigma about Aids, that touching or shaking hands with people with Aids would get infected, but Diana shook their hands and even sat close and comforted them. Besides that which is not less great than that, Diana shakes hands with lepers without gloves. Diana also bravely walked in the area that was landed by landmines in protest of landmines in Angola. Diana also often entertained friends who were in grief. Even though the princess was gone but the legacy that she gave to her children, worthy lessons about the life she taught in her children made them follow in her mother's footsteps so Diana's role in society remains until now.